Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer:
11) 6x^2+ 6x^3 = 6.x.x+6.x.x.x
12) -6x^2 + (-6) x^3 = -6.x.x + (-6).x.x.x
13) 5x - 8x = 5.x -8.x
Step-by-step explanation:
Let us solve the question one by one.
11) 6x^2+ 6x^3
In order to convert the polynomial in the factored form, we see which factors are common in all terms in the polynomial.
[tex]6x^2 = 6.x.x\\6x^3 =6.x.x.x[/tex]
The factored form is:
[tex]= 6.x.x+6.x.x.x[/tex]
12) -6x^2 + (-6) x^3
Similarly, as 11
[tex]-6x 2 =-6.x.x\\-6x^3=-6.x.x.x[/tex]
The factored form is:
[tex]=-6.x.x+ (-6).x.x.x[/tex]
13) 5x - 8x
We can clearly see that there is only one common factor in both terms which is x
[tex]5x = 5.x\\8x = 8.x[/tex]
The factored form is:
[tex]=5.x-8.x[/tex]
Hence,
11) 6x^2+ 6x^3 = 6.x.x+6.x.x.x
12) -6x^2 + (-6) x^3 = -6.x.x + (-6).x.x.x
13) 5x - 8x = 5.x -8.x
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.